Multiplex aspects in the construction of academic writer identity among ESL doctoral students - Lo, Yueh Yea; Juliana Othman,; Lim, Jia Wei (Penerbit Universiti Kebangsaan Malaysia, 2020)
Research in academic writing initially focuses on the output of writing, but it is now increasingly turned to writer identity. This article analyses how the acceptance of self as academic writers is difficult. The acceptance of self as an academic writer is quite complex, especially for first-year doctoral students who must engage with the demands of academic language in an academic context. Research acknowledges that self-acceptance as academic writers come with many implications and doctoral students are often hesitant to describe themselves as academic writers. This article seeks to address this complexity through empirical research focused on self-perception in the construction of an academic writer identity. This study involved ten first-year ESL doctoral students in the field of education at an established Malaysian institution. From the findings of this study, we identify four aspects that they experienced in becoming academic writers: creator, interpreter, communicator and academic presenter. These four aspects are experienced in different ways by each participant, illustrated by narratives of their life history and writing practice. In particular, it is hoped that this article can provide some pedagogical implications for the teaching of academic writing in institutes of higher education and offer a lens through which researchers and teachers of writing can further explore academic writer identi